Vibrio parahaemolyticus CadC regulates acid tolerance response to enhance bacterial motility and cytotoxicity - Gu, Dan (Journal of fish diseases, 2021)
© 2021 The Authors. Journal of Fish Diseases published by John Wiley & Sons Ltd.